Guyanese American Mental Wellness: A Phenomenological Study of Rupture and Resilience - John J. S. Harrichand; Shainna Ali; Aliya Subhit (COUNS-EDU: The International Journal of Counseling and Education, 2026)
Guyana has one of the highest suicide rates in the Western Hemisphere, yet the mental health experiences of Guyanese Americans remain underexamined. This study employed an interpretative phenomenological analysis and Relational Cultural Theory to explore how Guyanese Americans understand and navigate mental wellness. Thirty participants shared lived experiences through individual interviews and a follow-up focus group. Findings revealed two overarching themes: relational rupture and relational resilience, operating across interconnected personal, familial, and sociocultural levels. Relational rupture reflected experiences of emotional silence, stigma, and disconnection shaped by family dynamics, cultural expectations, and migration contexts. In contrast, relational resilience emerged through increased self-awareness, culturally responsive counseling, community connection, and generational boundary-setting. Implications are discussed for counselors seeking to provide culturally responsive, relationally attuned mental health care for Guyanese American clients.